(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
R. K. Narayan is a name that requires no introduction in English Literature. In the cosmos of Indian fiction authors who published in English, it seems like a glittering light. He spent more than 60 years as a novelist. He has received many distinctions and prizes, among them the AC Benson Medal from the Royal Society of Literature and the second highest civil award of India, Padma Vibhushan. Narayan was also nominated for the Indian Parliament’s upper house of Rajya Sabha. He is well known for his plain and unpretentious style of prose, frequently contrasted with William Faulkner. Much of his works reflect a profound curiosity in Hindu faith and myth. In this research article, a humble attempt has been made to analyze the way how Narayan accepts the Hindu Religion and Myth in the lives of his protagonists. He does not change or modernise myths but reveals their timeless significance as the most immediate aspect of human existence by their conceptual representation.